Edge Contrast of the FLAIR Hyperintense Region Predicts Survival in Patients with High-Grade Gliomas following Treatment with Bevacizumab - Bahrami, N.; Piccioni, D.; Karunamuni, R.; Chang, Y.-H.; White, N.; Delfanti, R.; Seibert, T.M.; Hattangadi-Gluth, J.A.; Dale, A.; Farid, N.; McDonald, C.R. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Treatment with bevacizumab is standard of care for recurrent high-grade gliomas; however, monitoring response to treatment following bevacizumab remains a challenge. The purpose of this study was to determine whether quantifying the sharpness of the fluid-attenuated inversion recovery hyperintense border using a measure derived from texture analysis—edge contrast—improves the evaluation of response to bevacizumab in patients with high-grade gliomas.MATERIALS AND METHODS: MRIs were evaluated in 33 patients with high-grade gliomas before and after the initiation of bevacizumab. Volumes of interest within the FLAIR hyperintense region were segmented. Edge contrast magnitude for each VOI was extracted using gradients of the 3D FLAIR images. Cox proportional hazards models were generated to determine the relationship between edge contrast and progression-free survival/overall survival using age and the extent of surgical resection as covariates.RESULTS: After bevacizumab, lower edge contrast of the FLAIR hyperintense region was associated with poorer progression-free survival (P = .009) and overall survival (P = .022) among patients with high-grade gliomas. Kaplan-Meier curves revealed that edge contrast cutoff significantly stratified patients for both progression-free survival (log-rank χ2 = 8.3, P = .003) and overall survival (log-rank χ2 = 5.5, P = .019).CONCLUSIONS: Texture analysis using edge contrast of the FLAIR hyperintense region may be an important predictive indicator in patients with high-grade gliomas following treatment with bevacizumab. Specifically, low FLAIR edge contrast may partially reflect areas of early tumor infiltration. This study adds to a growing body of literature proposing that quantifying features may be important for determining outcomes in patients with high-grade gliomas.ECedge contrastGBMglioblastomaGTRgross total resectionHGGhigh-grade gliomaMSRSMaximally Selected Rank StatisticsOSoverall survivalPFSprogression-free survivalRANOResponse Assessment in Neuro-OncologySTRsubtotal resectionVOLvolume